Mechanical, micro-structural and emission study of recycled aluminum based hybrid composites - Md. Mostafa Kamal; Durjay Saha; Md. Lobidh Prodhan; Md. Abdul Kader; Md. Bakhtierkhalzi; Md Shamimur Rahman Shanto; Md Asifur Rahman Sakib (Journal of Alloys and Metallurgical Systems, 2025)
The aerospace and automotive industries highly value aluminum matrix composites due to their superior mechanical properties, ability to be shaped and cast, lightweight, resistance to corrosion, and cost-effectiveness. This study focuses on the fabrication of an aluminum-based hybrid composite using recycled aluminum from beverage cans, reinforced with 2 wt% coconut shell ash (CSA) and varying proportions (2 wt%, 3 wt%, and 4 wt%) of rice husk ash (RHA) through the stir-casting technique. Optical emission spectroscopy (OES) was performed to confirm the chemical composition of the aluminum ingot obtained from the waste aluminum can. The distribution of reinforcement particles within the aluminum metal matrix was analyzed using Scanning Electron Microscope (SEM). Experimental tests were conducted on the fabricated hybrid composites to determine their mechanical properties, such as tensile strength, flexural strength, and Vickers Hardness The results showed that the presence of 4 % RHA in the composites containing 2 % CSA increases the hardness compared to the recycled aluminum. The highest hardness recorded was 105.9 HV, while the recycled metal had a hardness of 68.5 HV. The tensile and flexural strengths increased with the incorporation of reinforcements. However, at a concentration of 4 wt% RHA and 2 % wt% CSA, the tensile and flexural strengths began to decline due to the inhomogeneous mixing and aggregation of reinforcements within the aluminum matrix, as observed from SEM images. The composite material exhibited a maximum tensile strength of 96 MPa and a maximum flexural strength of 247.7 MPa at a concentration of 3 wt% RHA and 2 % wt% CSA. These findings highlight the potential of recycled aluminum and waste-derived green reinforcement to fabricate aluminum-based hybrid composite for advanced applications.